The Role of Artificial Intelligence in Collaborative Green Supply Chain Management: Impact on Company Performance and Moderation of Top Management Commitment - Franky Okto Bernando; Erick Lauren Ray; Benny Oktaviano (Jurnal Logistik Indonesia, 2025)
This study explores the growing interest in big data and Artificial Intelligence (AI) while addressing the gap in research on AI's role in Collaboration within Green Supply Chain Management (CGSCM) and its impact on Firm Performance (FP). Integrating AI and assessing Top Management Commitment (TMC) as a moderating factor, a moderated mediation model was constructed using data from 152 Indonesian manufacturing firms. The results show that AI positively influences CGSCM and FP, with CGSCM acting as a mediator between AI and FP. Additionally, TMC enhances the positive relationship between AI and CGSCM, strengthening this connection at higher TMC levels. Conversely, TMC moderates the link between AI and FP, reducing its strength at lower TMC levels. These findings provide valuable insights for supply chain and logistics managers, offering guidance on implementing AI to promote collaboration in sustainable supply chains and improve firm performance.